Lessons for supporting policy influencing in restrictive environments. Issue 5 (3rd July 2016) - Claessen, Anique; de Lange, Piet
ABSTRACT: Donors have rediscovered the importance of civil society in creating the political conditions for sustainable development. This article describes trends in diminishing space for civil society organisations (CSOs) and presents findings and lessons based on an evaluation of Dutch support for policy influencing. Restrictive environments for policy influencing engagement affect levels of effectiveness and threaten the sustainability of civil society. Aspects that are particularly important are civic engagement and cooperation between civil society actors. Building a strong support base is key, and local networks and international contacts are crucial. Furthermore, donors can help defend CSOs' operating space.